Drug exposure may have a substantial influence on COVID-19 prognosis among residents of long-term care facilities: an exploratory analysis. (August 2021) - Soldevila, Laura; Valerio-Sallent, Lluís; Roure, Sílvia; Pérez-Quílez, Olga; Mas, Miquel Àngel; Miralles, Ramón; López-Muñoz, Israel; Estrada, Oriol; Vallès, Xavier
Highlights: The consumption of drugs in elderly is highly prevalent Covid-19 heavily affected older people living in long-term care facilities Inhaled corticoids, ACE2 inhibitors and statins may have a protective effect Prevented attributable risk of these drugs towards mortality may be substantial Abstract: Objectives: To explore the association between drug exposure and SARS-CoV-2 prognosis among elderly people living in long-term care facilities (LTC) Design: We carried out a cross-sectional study among old people living in LTC that had a proven SARS-CoV-2 infection, including socio-demographic data, comorbidities and drug intake at the moment of the diagnosis. The study was focused on ACE2 inhibitors, ARA-II blockers, inhaled bronchodilators, oral corticoids, platelet antiaggregants, oral anti-coagulants, statins and Vitamin D. Results: 1 306 individuals were included, with a mean age of 86.7 years, and 72.3% were females. The case fatality rate was 24.4%. Among the studied exposures platelet antiaggregants were the most prevalent (24.7%). After adjusting for propensity score, the intake of inhaled corticoids (OR 0.73; p=0.03) and statins (OR 0.65; p=0.03) were found to be protective factors of death, whereas ACE2 inhibitor showed an almost significant association (OR 0.73, p=0.07). Conclusions: Considering the high prevalence of drug intake among elderly people, drug exposure may be an important Covid-19 disease modifier in LTC residents and should be considered when exploring prognostic risk factors associated to Covid-19.